Pengaruh Konten Pemasaran Instagram terhadap Minat Beli Pelanggan (Studi Kasus di Jordan Corner di Yogyakarta) - Kurniasari, Riza; Dus Reis Doa, Ajita Da Silva; Cahyono, Harry; Kon, Iknasius; Fadhilah, Muinah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to study the influence of marketing content on Instagram stories @jordancorner on customer buying interest. This research uses the Stimulus-Response (SR) theory. The method used is a quantitative method. To obtain data using a questionnaire distributed to respondents. The population in this study were all 97,700 followers of the Instagram account @jordancorner. This research uses random sampling techniques and simple linear regression. Processing questionnaire test data uses statistics products and service solutions (SPSS) software. The research results reveal that there is an influence of marketing content on Instagram stories @jordancorner on customer buying interest of 37.3% but in the weak category.